Improving the way healthcare professionals deliver different news to families during pregnancy or at birth: a qualitative study. (29th March 2021) - Mugweni, Esther; Goodliffe, Samantha; Jaswal, Sabrena; Walker, Melita; Emrys-Jones, Angela; Adams, Cheryll; Kendall, Sally
Abstract: Aim: To explore the lived experience of delivering or receiving news about an unborn or newborn child having a condition associated with a learning disability in order to inform the development of a training intervention for healthcare professionals. We refer to this news as different news. Background: How healthcare professionals deliver different news to parents affects the way they adjust to the situation, the wellbeing of their child and their ongoing engagement with services. This is the first study that examined the lived experience of delivering and receiving different news, in order to inform the development of training for healthcare professionals using the Theoretical Domains Framework version 2. Method: We conducted qualitative interviews with a purposive sample of 9 different parents with the lived experience of receiving different news and 12 healthcare professionals who delivered different news. It was through these descriptions of the lived experience that barriers and facilitators to effectively delivering different news were identified to inform the training programme. Data analysis was guided by Theoretical Domains Framework version 2 to identify these barriers and facilitators as well as the content of a training intervention. Findings: Receiving different news had a significant impact on parents' emotional and mental wellbeing. They remembered how professionals described their child, the quality of care and emotional support they received. The process had a significant impact on the parent–child relationship and the relationship between the family and healthcare professionals. Delivering different news was challenging for some healthcare professionals due to lack of training. Future training informed by parents' experiences should equip professionals to demonstrate empathy, compassion, provide a balanced description of conditions and make referrals for further care and support. This can minimise the negative psychological impact of the news, maximise psychological wellbeing of families and reduce the burden on primary care services.